Handbook of Advanced Magnetic Materials - Liu, Yi.; Sellmyer, David J.; Shindo, Daisuke; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
From high-capacity, inexpensive hard drives to mag-lev trains, recent achievements in magnetic materials research have made the dreams of a few decades ago reality. The objective of Handbook of Advanced Magnetic Materials is to provide a timely, comprehensive review of recent progress in magnetic materials research. This broad yet detailed reference consists of four volumes: 1.) Nanostructured advanced magnetic materials, 2.) Characterization and simulation of advanced magnetic materials, 3.) Processing of advanced magnetic materials, and 4.) Properties and applications of advanced magnetic materials The first volume documents and explains recent development of nanostructured magnetic materials, emphasizing size effects. The second volume provides a comprehensive review of both experimental methods and simulation techniques for the characterization of magnetic materials. The third volume comprehensively reviews recent developments in the processing and manufacturing of advanced magnetic materials. With the continuous search for new materials and invention of new processing routes, magnetic properties of materials now span a wide spectrum of soft magnetic materials, hard magnetic materials, recording materials, sensor materials and others. The fourth volume provides a comprehensive review of recent development of various newly emerging magnetic materials and their applications, along with a detailed description of the processing, properties and applications. Finally, with an eye to the future, the potential and limitation of the materials is addressed. Emphasis is on the processing, experimental investigation, theoretical understanding, and application of nanostructured magnetic materials. The chapters, authored by worldwide known specialists, provide an introduction into the topics and review the latest advances in magnetic nanostructures and materials. This includes emerging new materials, scientific methods, and experimental techniques. The coverage is very broad and includes nanostructural effects, characterization and simulation, fabrication and processing, and properties and applications of advanced magnetic materials. Each chapter will have an introduction to give a clear definition of basic and important concepts of the topic. The details of the topic are then elucidated theoretically and experimentally. New ideas for further advancement are then discussed. Sufficient references are also included for those who wish to read the original work. Many of the authors are well known senior scientists working in the field of magnetism and magnetic materials. This will be a valuable reference and research tool for graduate students and researchers in physics, materials science and chemistry to achieve an understanding of recent research developments in the field of magnetic materials. .
Intrinsic and Extrinsic Properties of Advanced Magnetic Materials -- Magnetism in Ultrathin Films and Beyond -- Classical and Quantum Magnetization Reversal Studied in Nanometer-Sized Particles and Clusters -- Micromagnetic Simulation of Dynamic and Thermal Effects -- Magnetic Relaxation and Quantum Tunneling of Magnetization -- Nanostructured Exchange-Coupled Magnets -- High-Field Investigations on Exchange Coupling in R-Fe Intermetallics and Hard/Soft Nanocomposite Magnets -- Fabrication and Magnetic Properties of Nanometer-Scale Particle Arrays -- Processing and Modeling of Novel Nanocrystalline Soft Magnetic Materials -- Advanced Magnetic Force Microscopy Tips for Imaging Domains -- Lorentz Microscopy and Holography Characterization of Magnetic Materials -- Characterization of Magnetic Materials by Means of Neutron Scattering -- Advanced Transmission Electron Microscopy of Nanostructured Magnetic Materials -- Mössbauer Spectroscopy Characterization of Soft Magnetic Nanocrystalline Alloys -- Atom Probe Characterization of Microstructures of Nanocrystalline and Nanocomposite Magnetic Materials -- Itinerant-Electron Metamagnetism -- Modeling of Hysteresis in Magnetic Materials -- Coarse-graining and Hierarchical Simulation of Magnetic Materials: the Fast Multipole Method -- Numerical Simulation of Quasistatic and Dynamic Remagnetization Processes with Special Applications to Thin Films and Nanoparticles -- Preisach Model and Simulation of Relaxation Kinetics -- Antiferromagnetism of Mn Alloys -- Characterization of Magnetic Materials by Means of Neutron Scattering -- HDDR Process for the Production of High Performance Rare-Earth Magnets -- Process and Magnetic Properties of Rare-Earth Bonded Magnets -- Laser Processing of Magnetic Materials -- Processing and Properties of Nanocomposite Nd2Fe14 B-Based Permanent Magnets -- Amorphous and Nanocrystalline Soft Magnetic Materials: Tailoring of Magnetic Properties, Magnetoelastic and Transport Properties -- Nanogranular Layered Magnetic Films -- Monodisperse Ferromagnetic Metal Particles: Synthesis by Chemical Routes, Size Control and Magnetic Characterizations -- Monocrystalline Half-Metallic NiMnSb Thin Films: Preparation and Characterization -- Bulk Amorphous Magnetic Materials -- Recent Developments in High-Temperature Permanent Magnet Materials -- New Rare-Earth Transition-Metal Intermetallic Compounds and Metastable Phases for Permanent Magnetic Materials -- Magnetic Properties and Interstitial Atom Effects in the R(Fe,M)12 Compounds -- Nanocrystalline Soft Magnetic Materials and Their Applications -- Spin-Density Waves and Charge-Density Waves in Cr Alloys -- New Magnetic Recording Media -- Magneto-Optical Properties of Nanostructured Media -- Magnetoresistive Recording Heads -- Magnetic Random Access Memories for Computer Data Storage -- Magnetoresistive Thin Film Materials and Their Device Applications -- Nano-Structural Magnetoelastic Materials for Sensor Applications -- Soft Magnetic Films and Wires for Magnetic Field Sensors -- Microwave Permeability of Magnetic Films.
Keywords: Physics; Optics; Electrodynamics; Magnetism; Magnetic materials; Electronics; Microelectronics; Optical materials; Electronic materials; Nanotechnology; Metals; Physics; Optics and Electrodynamics; Magnetism, Magnetic Materials; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Nanotechnology; Metallic Materials; Electronic books